Contact time and pH of the granadilla skin (Passiflora ligularis L.) in the zinc biosorption in the contaminated waters of the Rio Grande [Tiempo de Contacto y pH de la Cascara de Granadilla (Passiflora ligularis L.) en la Biosorción de Zinc en Aguas Contaminadas del Rio Grande] - Salas-Horna, Gerardo Lenin (2020)
ABSTRACT The purpose of this research was to evaluate the influence of contact time and pH on zinc biosorption of contaminated waters of the Rio Grande - Quiruvilca, using granadilla husks. Contaminated water was initially characterized by flame-type atomic absorption spectrophotometry, obtaining an initial concentration of 238.48 mg / L of zinc. The treatment was carried out at different times and pH, in order to determine the influence of said factors on zinc adsorption. At a pH 10 and a time of 24 minutes a final concentration of 0.09 mg / L was determined. The efficiency obtained is 99.96%, with an absorption capacity of 119.20 mg / g. The equilibrium data are properly adjusted to the Langmuir isotherm, so the zinc absorption kinetics that best suits the second order pseudo model.